Genre of the Acts of Paul: One Tradition Enhancing Another - Brock, Ann Graham (Apocrypha, 1994)
The Acts of Paul and Thecla (APITh) is crucial to determining the genre of the Acts of Paul. This paper will examine patterns of dialogue, as well as, literary and ideological fissures in the text of the APITh to show how Thecla, an independent Christian witness, has been subsumed under the authority of Paul. The APITh, then, is not a compilation of traditions about Thecla incorporated into traditions about Paul and Thecla, but is instead merely a grafting of Paul onto the Thecla legend. The author thus creates a literary composition modeled similarly to the gospels of the New Testament.